eTransformation in governance new directions in government and politics - Malkia, Matti; Anttiroiko, Ari-Veikko; Savolainen, Reijo (Gale virtual reference library, 2004)
Provides conceptual clarification of the e-transformation in governance, and presents empirical findings on the recent developments in Western countries.